2017
DOI: 10.1002/cncr.30870
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of proton‐beam radiation therapy for limited‐stage small cell lung cancer

Abstract: In the first prospective registry study and largest analysis to date of PBT for LS-SCLC, PBT was found to be safe with a limited incidence of high-grade toxicities. Cancer 2017;123:4244-4251. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 33 publications
0
29
2
Order By: Relevance
“…The comparatively low radiation esophagitis rates we report here may reflect treatment improvements over eras reflecting improved symptom prevention and proactive care, as well as advanced radiation treatment modalities. Importantly, to our knowledge, our series is the first machine learning analysis to include a cohort of patients treated with proton beam therapy, which may also result in lower than expected radiation esophagitis rates, as has been reported in locally advanced lung cancer prospective population treated with proton therapy [38]. Additionally, the lower than expected toxicity rates may contribute to a lack of reliable predictors in our models due to insufficient radiation esophagitis events.…”
Section: Discussionmentioning
confidence: 92%
“…The comparatively low radiation esophagitis rates we report here may reflect treatment improvements over eras reflecting improved symptom prevention and proactive care, as well as advanced radiation treatment modalities. Importantly, to our knowledge, our series is the first machine learning analysis to include a cohort of patients treated with proton beam therapy, which may also result in lower than expected radiation esophagitis rates, as has been reported in locally advanced lung cancer prospective population treated with proton therapy [38]. Additionally, the lower than expected toxicity rates may contribute to a lack of reliable predictors in our models due to insufficient radiation esophagitis events.…”
Section: Discussionmentioning
confidence: 92%
“…A possible reason for this result is that previous studies used large and 2-dimensional fields with elective nodal irradiation, which increased radiation exposure to normal tissues (9). At present, 3D-or intensity-modulated radiotherapy provides fewer, higher dose fractions and achieves similar results as the hyper-fractionated regimen (32). We suggest that future studies should use advanced radiotherapy techniques to determine the optimal dose and fractionation for limited-stage SCLC therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Although, there were no improvements in dose-volume indices for lung, PSPT significantly reduced the mean radiation dose to the heart (P=0.002). Similarly, other studies have demonstrated lower doses to the heart, but suggested that lower mean lung doses and V 20 could also be achieved with improving planning and delivery techniques over time (19,20).…”
Section: Editorialmentioning
confidence: 87%